Leaving matters: the nature, evolution and effects of emigration policies - de Haas, H; Vezzoli, S (International Migration Institute, 2011)
Debates on migration policies are strongly focused on immigration control, revealing a general receiving-country bias in migration research. To fill this gap, this paper reviews the nature, evolution and effects of emigration policies. Only a declining number of strong, authoritarian states with closed economies are willing and capable of imposing blanket exit restrictions. Paradoxically, while an increasing number of, particularly developing, countries aspire to regulate emigration, their capability to do so is fundamentally and increasingly limited by legal, economic and political constraints. The attitude of states is often intrinsically ambiguous, as they face a complex trade-off between the perceived economic and political costs and benefits of emigration, in which who leaves greatly matters. This motivates states to adopt more subtle policies to encourage or discourage migration of particular skill, gender, age, regional or ethnic groups. Since state policies simultaneously constrain and enable migration of different groups to different destinations, states can play a significant role in structuring emigration through influencing the (initial) composition and spatial patterns of emigration. Even 'laissez-faire’ policies require active state agency to create the structural conditions for 'free’ emigration. However, the effect of emigration policies on overall volume and long-term trends of migration seems limited or even insignificant because of the preponderance of other economic, social and cultural migration determinants. This review reveals the need to improve insights into how states and policies shape migration processes in their interaction with other migration determinants in sending and receiving countries.